2012
DOI: 10.5114/pjp.2012.32771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide synthase inhibitor (L-NAME) on cytopathologic changes due to cholestasis in hepatic cells of adult male rats

Abstract: Obstructive cholestasis is associated with overproduction of endogenous opioids, nitric oxide (NO) and cytokines in the blood stream. Nitro-L-arginine methyl ester (L-NAME) administration decreases the NO serum level and it is able to reduce related complications. The aim of this research is to survey the effects of the NO inhibitor on complications relating to cholestasis in liver cells and intrahepatic biliary ducts. We used five groups of animals: control, sham-operated (surgical control), bile duct ligated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…( 2011 ) demonstrated that inducible NO synthase (iNOS) is involved in the onset of fructose-induced liver steatosis and that the key factor in this process is the increased formation of reactive oxygen species in hepatic tissue. In mice receiving high amounts of fructose (Spruss et al ., 2011 ) or in rats with cholestasis (Monsef, 2012 ), various parameters indicating the status of inflammation and fibrosis in liver were ameliorated after treatment with unspecific NO synthase inhibitors like L-NAME, or in iNOS knockout mice. This may partially elucidate our observation of the failure of fructose administration to induce abnormalities in liver and plasma parameters in NO deficient rats.…”
Section: Discussionmentioning
confidence: 99%
“…( 2011 ) demonstrated that inducible NO synthase (iNOS) is involved in the onset of fructose-induced liver steatosis and that the key factor in this process is the increased formation of reactive oxygen species in hepatic tissue. In mice receiving high amounts of fructose (Spruss et al ., 2011 ) or in rats with cholestasis (Monsef, 2012 ), various parameters indicating the status of inflammation and fibrosis in liver were ameliorated after treatment with unspecific NO synthase inhibitors like L-NAME, or in iNOS knockout mice. This may partially elucidate our observation of the failure of fructose administration to induce abnormalities in liver and plasma parameters in NO deficient rats.…”
Section: Discussionmentioning
confidence: 99%